2018
DOI: 10.1111/jace.16176
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of Litchi‐like SrTiO3 with the help of ethylene glycol

Abstract: Templated by TiO2 microspheres, litchi‐like SrTiO3 crystals with a narrow size distribution and monodispersity were synthesized through the combination of regulating the ethylene glycol concentration during the hydrothermal process and the post heat treatment. The results show that when the volume ratio of water and ethylene glycol reached 10:70, microsized SrCO3 was firstly formed under the hydrothermal process, and then the litchi‐like SrTiO3 powder was obtained after the postheat treatment at 700°C for 4 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In the current investigation, the use of ethylene glycol presumably controls the growth rate of FeWO 4 and reduces the agglomeration degree of crystalline particles . The viscosity of ethylene glycol controls the order and growth rate of the structure blocks . A homogeneous distribution of Fe, W, and O was exhibited by the energy-dispersive X-ray spectroscopic (EDX) and subsequent elemental mapping (Figures b–e and S4, SI).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In the current investigation, the use of ethylene glycol presumably controls the growth rate of FeWO 4 and reduces the agglomeration degree of crystalline particles . The viscosity of ethylene glycol controls the order and growth rate of the structure blocks . A homogeneous distribution of Fe, W, and O was exhibited by the energy-dispersive X-ray spectroscopic (EDX) and subsequent elemental mapping (Figures b–e and S4, SI).…”
Section: Resultsmentioning
confidence: 74%
“…30 The viscosity of ethylene glycol controls the order and growth rate of the structure blocks. 31 A homogeneous distribution of Fe, W, and O was exhibited by the energy-dispersive X-ray spectroscopic (EDX) and subsequent elemental mapping (Figures 3b−e and S4, SI). The nanoscale morphological characteristics of the synthesized FeWO 4 were further studied by TEM analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Yang group used PVP with templating microspheres of TiO 2 to obtain litchilike SrTiO 3 structures in a hydrothermal setup. 41 After synthesizing SrTiO 3 by the solvothermal method, Zhao et al produced an SrTiO 3 –PVP thin film in which PVP acted as trapping centers for memory devices. The observed strong interaction between PVP and SrTiO 3 in thin films allowed promising results in device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that poly­(vinylpyrrolidone) (PVP) can easily bind to metal oxide surfaces to affect surface energy and influence crystal nucleation and growth. The Yang group used PVP with templating microspheres of TiO 2 to obtain litchilike SrTiO 3 structures in a hydrothermal setup . After synthesizing SrTiO 3 by the solvothermal method, Zhao et al produced an SrTiO 3 –PVP thin film in which PVP acted as trapping centers for memory devices.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] In this work, an environmentally friendly design scheme is used to prepare composite samples with a band-matching structure and a large specific surface area with a certain hierarchical structure. Based on our previous facile routes for preparing TiO 2 , BaTiO 3 , SrTiO 3 /TiO 2 microsphere particles evaluated from TiO 2 microspheric precursors, [23][24][25] mono-dispersed SrTiO 3 /TiO 2 (abbreviated as SrT) was used as the core material and modified by ZnO nanorod shell to form a rambutan-like structure. This method is expected to provide a new thought for synthesizing other ternary composites with band-matching structures that contributing to a better photocatalytic property.…”
Section: Introductionmentioning
confidence: 99%